Between rights and responsibilities : a fundamental debate / edited by Stephan Parmentier, Hans Werdmölder, Michaël Merrigan. - Parmentier, Stephan, 1960-; Werdmölder, Hans; Merrigan, Michaël, 1984- (Intersentia, 2016)
The last decade has witnessed increased criticism of the classical human rights paradigm for its obsession with the 'culture of claims and rights'. According to its critics, this culture has led to an obsession with the rights of individuals at the expense of focusing on groups and communities worldwide, and moreover, neglecting responsibilities and duties. It is also argued that the Western emphasis on the rights of individuals should be overcome by paying more attention to the responsibilities of individuals and collectivities as represented in other cultures of the world, and several documents have been drafted to this effect. These discussions, and the ensuing documents, are far from only theoretical or abstract but are grounded in day-to-day realities, as the ongoing debates on globalisation, multiculturalism, terrorism, and the like clearly illustrate.This volume comprises ten original chapters that were presented for the first time at a colloquium held at the Faculty of Law of the University of Leuven (Belgium) back in 2006, and subsequently reworked and fine-tuned over the years. Part I sets the scene of the debate about fundamental rights and fundamental responsibilities, while in Part II the implications of an emphasis on responsibilities, duties and obligations are concretised in specific areas and through specific cases. This book cannot answer all the questions posed by the changing realities of rights and responsibilities in today's world, which is undergoing profound changes. However, it does aim to shed new light on important problems related to some of the major transformations occurring in European and Western societies and the ensuing changes in philosophical, political, social and legal thinking. It is therefore directed to academics, as well as policy-makers at various levels, the media and any person interested in a deeper understanding of new challenges for the modern world.